THE LAW ON FREE ACCESS TO INFORMATION OF PUBLIC CHARACTER AND ITS RESPECT FROM THE JUDICIAL COUNCIL OF RN MACEDONIA - Veljanovska, Svetlana; Dukoski, Sasha (Horizons - International Scientific Journal, 2021)
The functioning of the judiciary authority is important for each state but above all for each individual citizen. It is for these reasons that the need to assess the openness, publicity and transparency of the judiciary power in the Republic of North Macedonia is evident.The paper is based on the assumption that openness, publicity and transparency contribute to combating corruption in the judiciary and the state, improving the daily lives of citizens, and increasing trust in institutions, ie the judiciary. It deals with open situation, publicity and transparency of the Judicial Council as an independent and autonomous body of the judiciary in charge of ensuring and guaranteeing the independence and autonomy of the judiciary. The paper examines the legal (constitutional, legal and by-law) and institutional framework for an open, transparent and participatory Judicial Council in compliance with the Law on Free Access to Public Information, which is wide enough to enable transparent and participatory functioning of judicial institutions and power.